Procesos cognitivos implicados en la conciencia fonológica para el desarrollo de la lecto- escritura, en los estudiantes de 4to año de Educación general básica paralelo “A” de la Unidad educativa Ángel Polibio Chaves en la ciudad de Guaranda. - Andrade Solis, Paola Elizabeth (2022)
This research work shows the impact of the limited knowledge of the cognitive processes involved in phonological awareness for the development of reading and writing, since, due to the context of virtual education, these aspects are not efficiently attended. The basis of this study were the students of the 4th year of General Basic Education of the Ángel Polibio Chaves Educational Unit in the city of Guaranda, where a learning gap could be evidenced in relation to the contents of reading and writing exposed by the national curriculum. For this reason, the purpose of this research is to analyze and strengthen the knowledge of the cognitive processes immersed in phonological awareness for the development and strengthening of reading and writing in children, through different teaching strategies and the application of educational software. Consequently, it is shown that the difficulties encountered with respect to reading and writing were progressively improved. In addition, because the research was developed based on a mixed approach, it was possible to obtain greater veracity in the data collected through surveys, interviews and discussion groups. Finally, the results show that the learning and development of reading and writing during the first years of formal education are essential knowledge that must be guaranteed at the corresponding level by all educational institutions for the improvement of the teaching-learning process in higher grades.